Prevalence and phenotypic findings of pathogenic or likely pathogenic copy number variants in 10,537 pregnancies - Shiwei Ren; Wenjing Gu; Ting Liu; Jinyan Yan; Haixin Dong; Chuchu Niu; Lizhu Guo; Huan Guo (PLoS ONE, 2025)
Background Pathogenic and likely pathogenic copy number variations (p/lpCNVs) detected through chromosomal microarray analysis (CMA) are crucial for understanding the etiology of birth defects. However, due to incomplete penetrance and variable phenotypic expression, the intrauterine phenotypic characteristics and genotype-phenotype correlations of these variations remain unclear. Therefore, this study aims to explore the prevalence and clinical implications of p/lpCNVs in a large cohort of pregnant women. Methods and findings This study retrospectively analyzed 10,537 prenatal diagnostic cases from 2013 to 2022 at the Affiliated Hospital of Jining Medical University. All pregnant women underwent amniocentesis and chromosomal microarray analysis (CMA). Cases were divided into two groups: the CMA group (194 cases) and the karyotype analysis group (259 cases), based on whether CNVs could be detected by traditional karyotype analysis. The primary study outcomes included the incidence of pathogenic or likely pathogenic CNVs, the distribution of variations in specific chromosomal regions, and the correlation between these variations and clinical phenotypes (e.g., cardiovascular abnormalities, developmental delays). Statistical analyses were performed using the chi-square test and the Mann-Whitney U test, with p < 0.05 considered statistically significant. Among 7,663 amniocentesis CMA cases, 453 cases of pathogenic or likely pathogenic CNVs were identified, with 194 cases in the CMA group and 259 cases in the karyotype analysis group. Specific chromosomal regions, such as 22q11.21 and 16p13.11, were associated with clinical phenotypes such as cardiovascular abnormalities and developmental delays. The incidence of pathogenic CNVs was higher in pregnant women with polyhydramnios and those conceived via assisted reproductive technology (ART). The main limitation of this study is the lack of long-term follow-up data on the clinical outcomes of pathogenic CNVs. Conclusions This study demonstrates for the first time that chromosomal microarray analysis (CMA) is superior to traditional karyotype analysis in high-risk pregnancies, especially in those with a single clinical indication, by more effectively detecting small copy number variations. Pathogenic CNVs are more likely to cause structural abnormalities, highlighting the stronger association between pathogenic variations and significant phenotypic consequences. Our data also suggest that factors such as assisted reproductive technology (ART) and polyhydramnios may be associated with the occurrence of p/lpCNVs. Future research should focus on clarifying the genotype-phenotype correlations of p/lpCNVs and exploring the potential impact of ART on genetic variations. Long-term longitudinal studies will help deepen the understanding of these variations’ long-term effects on maternal and fetal health, ultimately improving prenatal diagnostics and genetic counseling.